Facebook's mobile career. (November 2014) - Goggin, Gerard
At the end of its first decade, Facebook's identity, popularity and characteristics are shaped in important ways by its becoming a form of mobile media. This article seeks to explore and understand Facebook as the important force in mobile media and communication it now is. It draws upon and combines perspectives from technology production, design and economy, as well as user adoption, consumption, practices, affect, emotion and resistance. This article discusses the beginnings of mobile Facebook and the early adoption of mobile Facebook associated with the rise of smartphones. The second part of the article explores Facebook's integration with photography (with Instagram) and social games (such as Zynga's Farmville ). This article argues that Facebook's mobile career is an accomplishment that has distinctively melded evolving affordances, everyday use across a wide range of settings, as well as political economies, corporate strategy and design.